2016
DOI: 10.5301/uro.5000178
|View full text |Cite
|
Sign up to set email alerts
|

Level of Copper in Human Split Ejaculate

Abstract: This study concluded that copper was released from throughout the genital tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…44 Origin of different electrolytes and metals present in semen was identified by using split ejaculation technique. [44][45][46][47][48] Individual and within subject variability in semen element is also reported. 49 Several workers interested in the study of elements in semen reported the level of different elements like sodium, potassium, calcium, magnesium, 38,50,51 iron, 52 zinc, 39,53 copper, 54,55 cadmium, chromium, nickel and lead.…”
Section: Discussionmentioning
confidence: 99%
“…44 Origin of different electrolytes and metals present in semen was identified by using split ejaculation technique. [44][45][46][47][48] Individual and within subject variability in semen element is also reported. 49 Several workers interested in the study of elements in semen reported the level of different elements like sodium, potassium, calcium, magnesium, 38,50,51 iron, 52 zinc, 39,53 copper, 54,55 cadmium, chromium, nickel and lead.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to get consent from patients as this is a retrospective study. Usually laboratories advice patients to collect semen without missing any drop 20 for examination after maintaining an abstinence of 2-5 days. 21,[22][23][24] Semen parameters are influenced by external temperature and daylight duration.…”
Section: Methodsmentioning
confidence: 99%
“…Detected Analyte LOD Analytical Tool [19] Cd and Pb n.a FAAS [27] Cd and As As: 0.05 µg/L and Cd: 0.002 µg/L AAS [28] Cu n.a AAS [29] Cd and Zn Zn: 6.6 mg /L FAAS [32] Fe n.a AAS [35] Cd, Zn, and Pb n.a AAS, GFAAS, and FAAS [41] Pb n.a GFAAS [42] Zn and Cu n.a AAS [43] Cd, Zn, Se, Pb, and Cu n.a ETA-AAS [46] Fe and Cd n.a AAS [47] Zn n.a FAAS [48] Zn n.a AAS [49] Pb n.a GFAAS [56] Fe, Zn, Cu, and Mg n.a AAS [57] Cd and Pb Pb: 0. Cd, Se, and Pb n.a AAS [67] Fe, Zn, Se, Cu, Ca, and Mg n.a FAAS [68] Zn, Mn, and Cu n.a AAS [69] Zn n.a AAS [70] Zn and Se Zn: 0.47µg/L and Se: 0.78µg/L AAS and FAAS [71] Zn n.a AAS [72] Cr and Co 0.02 mg/L ETA-AAS [73] As, Cd, Cu, Pb, Se, and Zn As: 2.59, Cd: 0.03, Cu:1.03, Pb: 0.98, Se: 0.02, and Zn: 0.065 µg/L AAS, ETA-AAS, and HGAAS [74] Cd, Zn, Pb, Cr, and Cu n.a AAS [75] Cd and Pb n.a FAAS [76] Zn n.a AAS [77] Cd, Pb, and Cr n.a AAS AAS: atomic absorption spectroscopy, ETA-AAS: electrothermal atomization -atomic absorption spectrometry, FAAS: Flame atomic absorption spectroscopy, GFAAS: graphite furnace atomic absorption spectrometry, HGAAS: Hydride generation atomic absorption spectroscopy, n.a: not available.…”
Section: Refunclassified